(untitled) (Ustozlar uchun, 2026)
Tourism discourse serves as an important medium for promoting destinations, shaping cultural images, and influencing travelers’ perceptions. This article presents a comparative analysis of English and Uzbek tourism discourse, examining their linguistic, cultural, and communicative characteristics. Through the analysis of tourism brochures, websites, and promotional materials, the study identifies key similarities and differences in vocabulary, stylistic features, and persuasive strategies. The findings reveal that English tourism discourse is generally characterized by global accessibility and persuasive marketing techniques, whereas Uzbek tourism discourse places greater emphasis on cultural heritage, hospitality, and national identity.